An Investigation Of The Oil Price Risk Factor And Macroeconomics Variables In The Asean Stock Market - Ansarifar, Alireza (2009)
This study examine the influence of macroeconomic risk factors namely Oil price changes, world market returns, and exchange rates volatilities on ASEAN Markets.